The Poetics of Time and Space in Abdullah Ibrahim - Vos, Stephanie (Schweizer Jahrbuch für Musikwissenschaft, 2026)
Time is a prominent theme in South African pianist Abdullah Ibrahim’s writing, discourse and music. His elaborations of time converge with ideas about place – a fact that assumes significance, given that he was away from South Africa while developing his aesthetic, in what would later cement into exile. This paper looks at the imaginative ways in which he deploys time as a metaphor for place, both in his writing and in his music between 1965 and 1970. Through a discussion of time as a theme in his discourse, the blurring of time and place in stories and memory, and finally in tracing the ways this finds expression in the tracks “Pye R Squared” and “Heyt Mazurki” (both released in 1965), the article attends to the political commitments that inhere in Ibrahim’s poetics of time and space, and suggests how resistance might be read in the imaginative elaboration of time and space in one musician’s work during exile.